2020
DOI: 10.4317/jced.56006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-office bleaching gels with calcium or fluoride on color, roughness, and enamel microhardness

Abstract: Bleaching gels with remineralizing agents e116

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 22 publications
5
36
0
4
Order By: Relevance
“…Studies have shown that the addition of fluorine to the bleaching gel reduces microhardness loss in enamel 41 and does not alter surface roughness 42 . In alignment with this information, the high concentration Opalescence Boost PF 40% HP bleaching agent used in our study showed microhardness and surface roughness values similar to those of lower concentration agents, which can be explained by its inclusion of sodium fluoride.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that the addition of fluorine to the bleaching gel reduces microhardness loss in enamel 41 and does not alter surface roughness 42 . In alignment with this information, the high concentration Opalescence Boost PF 40% HP bleaching agent used in our study showed microhardness and surface roughness values similar to those of lower concentration agents, which can be explained by its inclusion of sodium fluoride.…”
Section: Discussionsupporting
confidence: 86%
“…Apesar de seguro, alguns efeitos adversos transitórios são associados a esse tratamento, como a sensibilidade dental 5 e alteração das propriedades físico-químicas dos tecidos dentários 14 . Apesar de o gel utilizado na primeira sessão clareadora ser seguro e validado pela literatura, a troca por outro gel que tinha em sua composição uma menor concentração de peróxido de hidrogênio associado ao gluconato de cálcio foi baseada em um estudo prévio que sugeriu o uso desses géis para diminuir a sensibilidade durante o tratamento clareador de consultório 12 sem perder a eficácia clareadora ou promover alterações na microdureza do esmalte 13 . No presente caso, a troca dos géis promoveu uma diminuição do relato da sensibilidade após a consulta clínica pela paciente, entretanto esse achado deve ser validado por futuros ensaios clínicos controlados e randomizados.…”
Section: Discussionunclassified
“…Bleaching gels with higher peroxide concentrations (30-35%) are used in professional bleaching sessions under the direct supervision of a dentist. The high peroxide concentration in the bleaching gel, such as 35% hydrogen peroxide, results in a faster whitening effect but it also has a potentially higher risk of adverse effects such as tooth sensitivity and morphological changes in the enamel (Dey et al, 2016;Ayres et al, 2016;Vieira et al, 2020).…”
Section: Medmentioning
confidence: 99%
“…The bleaching technique is acidic and may demineralize the enamel. When hydrogen peroxide degrades, it releases free radicals (byproducts of the hydroxyl OH and perihydroxyl OH2 reaction) that can diffuse through the tooth enamel structure and oxidize particles responsible for enamel darkening in both intraprismatic region and prism peripheries, converting them into smaller molecules and changing the optical properties of the tooth substrate (Liporoni et al, 2020;Vieira et al, 2020). It is still not well established how free radicals diffuse but their infiltration through the enamel structure is associated with the increased permeability of this tissue.…”
Section: Medmentioning
confidence: 99%
See 1 more Smart Citation